ESTUDIOS HELMINTOLOGICOS DE LA REGION ONCOCERCOSA DE MEXICO Y DE LA REPUBLICA DE GUATEMALA TREMATODA II PRESENCIA DE PARAGONIMUS EN RESERVORIOS NATURALES Y DESCRIPCION DE UN NUEVO GENERO HELMINTHOLOGICAL STUDIES IN THE ONCHOCERCIASIS REGION OF MEXICO A - CABALLERO Y C, EDUARDO; C, EDUARDO (Instituto de Estudios Médicos y Biológicos, CD MEXICO, DF, MEX, 1946)
Discussion of the methods recommended for the benefit of the coffee in several Central and S American countries, followed by the description of a modification introduced by the author and based on precipitation of the pectins in form of Ca pectate
ANS INST BIOL
Keywords: ESTUDIOS, HELMINTOLOGICOS, MEXICO, GUATEMALA, PRESENCIA, PARAGONIMUS, DESCRIPCION, NUEVO, GENERO; CIENCIAS MEDICAS; SALUD PUBLICA